Is antibody-drug conjugate a rising star for clinical treatment of solid tumors? A systematic review and meta-analysis. (September 2022) - Zhang, Leyin; Shen, Deyi; Yu, Lulin; Yan, Yici; Wasan, Harpreet S.; Yu, Jieru; Zhang, Shuo; Sun, Leitao
Abstract: Antibody-drug conjugates (ADCs) show significant advantages in cancer treatment due to their high selectivity and anti-tumor activity, but the efficacy and safety of the treatment of solid tumors are unknown. We searched research databases, major conference proceedings and trial registries for randomized controlled trials (RCTs). Then, we selected qualified studies and extracted dates. Studies were assessed for quality, and a meta-analysis was conducted to quantify effects of ADCs on overall survival (OS), progression-free survival (PFS), overall response rate (ORR) and adverse events (AEs). The within-study heterogeneity was evaluated by subgroup and sensitivity analysis. Eleven RCTs with 4353 participants were included. ADCs had better PFS (HR: 0.69, 95 % CI: 0.56–0.82) and OS (HR: 0.76, 95 % CI: 0.61–0.92). ADCs resulted in lower risk of febrile neutropenia in blood system. Conversely, ADC therapy had not a prepotent on ORR (RR: 1.36, 95 % CI: 0.71–2.60). Highlights: Our systematic review and meta-analysis included 11 randomized controlled trials. Antibody drug conjugates showed better survival benefit for solid tumor patients. Antibody drug conjugates had no advantage in overall response rate. Non-first-line treatment of tumors with visceral metastasis were benefited more. The toxicities of antibody drug conjugates required management.